A Sociolinguistic Analysis of Slang Words Used in Pulp Fiction Movie Directed By Quentin Tarantino - Ryanda, Muhammad Abdil Ghiffari; Pratama, Rizky Mirani Desi (Universitas Dian Nuswantoro, 2024)
This research was conducted by analysing slang language in the script of